Experimental and numerical investigation and homogenization of flow distribution in the ventilation system of a passenger vehicle - Erdem, Muhammet Yusuf; Demir, Hakan; Terzioglu, Halit; Gemici, Zafer (ELSEVIER SCIENCE INC, 2026)
Achieving homogeneous airflow distribution in passenger vehicle HVAC systems is critical for thermal comfort and energy efficiency, yet accurate validation remains challenging due to complex duct geometries and high turbulence. This study presents a comprehensive experimental and numerical investigation to optimize flow distribution and establish a robust measurement methodology. Experimental measurements were conducted at three fan speeds (low, medium, high) using both vane and hot-wire anemometers. The comparative analysis revealed that vane anemometers provide superior accuracy in measuring turbulent outlet flows, whereas hotwire anemometers exhibited significant deviations exceeding 15-20% due to the multi-directional nature of the discharge flow. Numerical simulations were performed using Computational Fluid Dynamics (CFD) with the k-epsilon Realizable turbulence model. It was demonstrated that the Rigid Body Motion (RBM) technique yielded significantly higher concordance with experimental data compared to the Moving Reference Frame (MRF) method, reducing the deviation in total flow rate to approximately 8-10%. Following validation, a geometric optimization was introduced by integrating a 9 mm obstruction geometry into the centre duct. This modification successfully balanced the flow, achieving a uniform distribution ratio of approximately 25% across all four vents. The study contributes to the literature by defining a reliable measurement protocol for automotive ducts and demonstrating an effective geometric optimization strategy for flow homogenization.
Keywords: Automotive HVAC; Flow uniformity; CFD validation; Vane anemometer; Hot-wire anemometer; Geometric optimization; Rigid Body Motion (RBM); AIR; SIMULATION; Thermodynamics; Engineering; Mechanics